Marker-less deletion of cctA gene of Clostridium chauvoei. (February 2020) - Gupta, Sanjay Kumar; Dixit, Sameer; Dangi, Saroj K.; Kaur, Gurpreet; Mashooq, Mohmad; Karthik, Kumaragurubaran; Sarkar, Mihir; Mahajan, Sonalika; Nagaleekar, Viswas Konasagara
Abstract: Clostridium chauvoei causes blackleg disease in domestic animals, especially cattle and sheep. The pathogen produces several toxins including CctA – a hemolysin and protective antigen. Molecular pathogenesis of the disease is poorly understood, possibly due to lack of genetic manipulation tools for C. chauvoei . In the present study, we report the marker-less deletion of cctA gene using the CRISPR-Cas9 system. The C. chauvoei cctA deletion mutant had negligible hemolytic and significantly reduced cytotoxic activities. To the best of our knowledge, this is the first report of genetic manipulation of C. chauvoei. The method we used in this study can be applied for genetic manipulation of C. chauvoei to better understand the pathogenesis and genetics of the pathogen. Highlights: The markerless deletion of cctA gene that encodes hemolysin protein of Clostridium chauvoei was accomplished. Δ cctA mutant showed negligible hemolysis and significantly reduced cytotoxicity. This is the first report of genetic manipulation of C. chauvoei. The method helps in development of mutants of C. chauvoei to study pathogenesis and in the advancement of prophylactics.